Formulation and in-vitro characterization of floating sustained-release tablets of metformin hydrochloride - Senjoti, Faria Gias; Md. Jaffri, Juliana; Mandal, Uttam Kumar (2014)
Metformin HCl, a drug from biguanide class, is the most commonly used first-line antihyperglycemic agent in the treatment of NIDDM [1]. The major problems associated with the drug are high dose (1.5-2.0 g/day), frequent dosing due to its shorter biological half-life (1.5-4.9 hr), and low bioavailability (60%) [2]. Low bioavailability of metformin results from incomplete absorption of the drug as metformin is majorly absorbed from the stomach and lower part of GIT [3]. An oral sustained-release floating tablets of metformin HCl based on gas formation and swelling was developed to prolong gastric residence time and increase drug bioavailability. Sustained-release floating tablets of metformin was fabricated with Polyethylene oxide (PEO) and HPMC as polymers, SSG as swelling enhancer, NaHCO3 as effervescent component, PVPK as binder, Magnesium stearate as lubricant and Talc as glidant. Thirteen trial formulations (Table 1) were investigated according to Box-behnkhen experimental design taking various composition of SSG, NaHCO3 and combination of HPMC and PEO at three levels in order to find out the best formulation depending on floating lag time and in-vitro release profile. 12 mm circular bi-convex floating tablets were prepared by wet granulation method using a 10-station Rotary tablet press machine (Mini press II, Remek). Pre-compression parameters of the granules like bulk density (BD), tapped density (TD), compressibility index, angle of repose etc were tested as part of pre-formulation study. Drug-excipient compatibility was confirmed by DSC (DSC 821e, Mettler Toledo, Switzerland) and X-ray diffraction (Perkin Elmer RX-1) study. Tablets were evaluated for weight variation, hardness, thickness, friability, moisture content, assay, in-vitro floating lag time, % swelling etc. In vitro drug release for trial formulations and market formulation (Glucophase® XR by Merck Sante S.A.S.) was studied for 12 hr using a USP Type I dissolution apparatus (basket) with 100 rpm and 900 ml 0.1 N HCl as dissolution medium maintained at 37 ± 0.5 0C. Released metformin HCl amounts were determined UV-spectrophotometrically by measuring the absorption at 232 nm and calculated using calibration curves of the drug (Fig. 1). In vitro release mechanism was evaluated by linear regression analysis. The SEM images of the tablet were taken before and after in vitro dissolution study for both outer and inner cross-sectional surface. Tablets from the optimized formulation determined by response surface methodology (RSM) were stored at accelerated stability condition (40 °C and 75% RH) for 3 months. Content of metformin, drug release profile and buoyancy in 0.1N HCl of stored tablets were compared with the initial data. All pre-formulation parameters were found to be within acceptable range. Fabricated tablets showed acceptable weight variation, hardness, thickness, friability and uniformity of drug content. Melting peaks of metformin was visible in DSC thermogram of drug-excipients mixture (Fig. 2), indicating that metformin was compatible with the rest of the excipients of formulation. FTIR graphs (Fig. 3) also confirmed the same finding. Floating lag time and duration of floating were found to be dependent on amount of gas effervescent agent (NaHCO3), swelling of polymers (HPMC and PEO) and swelling enhancer (SSG). The optimized formulation was found to provide average floating lag time less than 4 minutes with a floating duration of more than 24 hours. Swelling rate of the combination of polymers was found to be rapid and linear for initial 2 hr, however it decreased thereafter and maintained the linearity until 8 hours (Fig. 4). Combination of HPMC and PEO allowed efficient control of drug release for 12 hr which was similar (f2 value 68) to that of market sample (Fig. 5). SEM figure (Fig. 6) showed the non-porous nature of tablet outer surface and little bit porous structure of inner surface before dissolution study. However, after dissolution of 2 hr and 8 hr, both surfaces turned into porous structure which allows the drug to diffuse to the surrounding medium. This also proves that the drug release occurs by diffusion. Based on accelerated stability study optimized formulation was found to be stable for three months without any major changes in assay, dissolution profile, floating lag time and other physical properties.